Critical analysis of the use of the rubric for research methodology - Alcántara Gutiérrez, María Esther; Ramírez Martínez, Mireya (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this paper, a critical analysis is formulated on the use of Rubrics during the co-evaluation exercises among peers on their performance in the research developed in postgraduate studies. The interviews with students and teachers show how the understanding of the academic description of the result of the application of the methodology is deepened and broadened, due to the contrasting observation of one’s own work with the performance of others, in accordance with the of teaching of the research methodology proposed by Alcántara and Ramírez (2022).